Penerapan Kontrol Kualitas Produk Sponge Cake di Pastry Section Harris Hotel & Conventions Bundaran Satelit Surabaya - Azhalia Sukma Putri; Niken Purwidiani; Lucia Tri Pangesthi; Lilis Sulandari (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
This study explores the implementation of quality control for sponge cake products in the Pastry Section of Harris Hotel & Conventions Bundaran Satelit Surabaya. The primary objective is to analyze how quality control is applied across raw materials, production processes, and product presentation. Using a descriptive qualitative method, data were collected through in-depth interviews, direct observations, and documentation. Findings reveal that raw material quality control includes inspecting quality, maintaining recommended storage temperatures, and utilizing FIFO (First In, First Out) and FEFO (First Expired, First Out) systems. The production process adheres to standardized recipes and precise oven temperature settings to ensure consistent results. Mixing and baking are carried out with attention to detail to minimize errors. Presentation emphasizes aesthetic appeal, including the addition of garnishes, to enhance visual attractiveness. The study also highlights the importance of staff training in maintaining consistent quality control. In conclusion, effective quality control not only improves product quality but also enhances customer satisfaction, which is critical for success in the hospitality industry. Recommendations include enhanced staff training, SOP updates, and stricter supervision to maintain quality standards.